Refractory human cytomegalovirus infection without evidence of genetic resistance in the UL-54 and UL-97 genes in a pediatric hematopoietic stem cell transplant recipient: a case report - Alejandra Pando-Caciano; Ketty Adid Escudero-Ramirez; Jackeline Carol Rodríguez-Torres; Holger Maita-Malpartida; Holger Maita-Malpartida (Frontiers in Medicine, 2024)
Cytomegalovirus (CMV) infection is a common complication in patients undergoing hematopoietic stem cell transplantation (HSCT). Management of refractory CMV infections, especially in developing countries, can be challenging due to the limited availability of second and third-line antiviral drugs or alternative treatments. Here, we present a case of an 8 years-old patient diagnosed with acute myeloid leukemia. Eight months post-diagnosis, the patient underwent TCR-αβ+/CD19+-depleted haploidentical HSCT. Both the donor and recipient tested positive for anti-CMV IgG and negative for IgM antibodies. Before transplantation, the patient received CMV prophylaxis in the form of intravenous ganciclovir. Post-transplantation, the patient exhibited oscillating CMV viral loads and was diagnosed with a refractory infection. Treatment with ganciclovir, foscarnet, and cidofovir was unsuccessful. Sequencing of UL-54 and UL-97 genes was performed to rule out potential resistance to first-line treatment. Ten months after the HSCT, the child died from hypovolemic shock due to gastrointestinal bleeding. This is the first case reported in Peru and Latin America of a refractory CMV infection in a pediatric HSCT recipient without evidence of clinical symptoms and CMV genetic resistance. This case demonstrates the need for alternative treatments to manage refractory CMV infections, especially in haploidentical HSCT cases where drug resistance is frequent (~15%). Furthermore, this case highlights the importance of using highly sensitive genetic tools to detect mutations associated with virus resistance in a broader range of the viral genome.